1985
DOI: 10.1093/jac/16.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenoxymethylpenicillin and erythromycin prophylaxis on anaerobic bacteraemia after oral surgery

Abstract: The effect of antibiotic prophylaxis on bacteraemia was assessed in 60 oral surgery operations. Fifty-one patients were divided in three groups receiving a 2 g dose of phenoxymethylpenicillin, a 0.5 g dose of erythromycin or no prophylaxis. During operation, the total numbers of bacteria were lower in the antibiotic groups than in the non-treatment groups (P less than 0.05). The number of patients with anaerobic bacteraemias, however, were similar in all three groups. The incidences of bacteraemia 10 min after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 15 publications
2
17
1
Order By: Relevance
“…In contrast, Takai et al (2005) found similar percentages of positive postextraction blood cultures between patients treated under general anaesthesia and those treated using local anaesthesia (57.7% and 58.1% respectively). The prevalence of B‐TME detected in the present series was similar to that reported in previous studies performed under local anaesthesia (Josefsson et al , 1985; Heimdahl et al , 1990).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, Takai et al (2005) found similar percentages of positive postextraction blood cultures between patients treated under general anaesthesia and those treated using local anaesthesia (57.7% and 58.1% respectively). The prevalence of B‐TME detected in the present series was similar to that reported in previous studies performed under local anaesthesia (Josefsson et al , 1985; Heimdahl et al , 1990).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, although the influence of the number of third molars extracted on the prevalence of B-TME at 15 min was not analysed in our series (because all but two patients underwent three to four third molar extractions), the duration of the surgical intervention was similar in the patients with positive blood cultures at 15 min and in those with negative blood cultures. This result is in agreement with the findings of Josefsson et al (1985) who studied the influence of surgical time on the prevalence of B-TME, detecting no correlation between the two variables.…”
Section: Oral Health Statussupporting
confidence: 92%
See 1 more Smart Citation
“…The power of the study was calculated by comparing the "prevalence of bacteremia" obtained at 30 s after the dental extractions between a preliminary control group (n ϭ 14) and a preliminary AMX group (n ϭ 12), CLI group (n ϭ 15), and MXF group (n ϭ 12). The prevalence of bacteremia in this control group was 93%, that in the AMX group was 58% (statistical power, 0.6; estimated sample size, 21), that in the CLI group was 87% (statistical power, 0.08; estimated sample size, 392), and that in the MXF group was 42% (statistical power, 0.8; estimated sample size, 11).…”
Section: Methodsmentioning
confidence: 78%
“…Oral clindamycin was found to decrease the risk of bacteremia by 15%, from 88% to 74.9% 36,[39][40][41] . Although oral penicillin has been reported to decrease the risk of bacteremia by just 32%, from 66.7% to 45.1% 31,33,42,43 , intravenous or intramuscular penicillin decreased the risk of bacteremia by 68%, from 56.7% to 18% [42][43][44][45] . To our knowledge, neither oral cephradine nor cephalexin has been studied in randomized controlled trials for the prevention of bacteremia with dental procedures.…”
Section: Guidelines From Professional Societiesmentioning
confidence: 98%